Lung adenocarcinoma expressing receptor for advanced glycation end-products with primary systemic AL amyloidosis: a case report and literature review - Okamoto, Shouichi (BMC Cancer, 2017)
BACKGROUND: Receptor for advanced glycation end-products (RAGE), a receptor for amyloids, is constitutively expressed in lungs and generally observed to be downregulated in lung cancer tissues. However, increasing levels of RAGE or serum amyloids is associated with poor outcome in lung cancer patients. We report a rare case of primary systemic amyloid light-chain (AL) amyloidosis in biopsy-proven multiple organs with early-stage non-small cell lung cancer (NSCLC) that displayed strong staining for RAGE in the tumour tissue. Interestingly, compared with randomly selected lung cancer biopsy samples, including all representative histological subtypes of NSCLC and small-cell lung cancer, only the NSCLC in the present case showed strong expression for RAGE that can bind amyloids. CASE PRESENTATION: A 71-year-old woman was admitted to our hospital for comprehensive investigation of nephrotic syndrome. Computed tomography showed a small nodule in the right upper lung lobe with hilar mediastinal lymph node enlargement. Pathological examination of transbronchial biopsy samples of the nodule yielded a diagnosis of lung adenocarcinoma. Furthermore, the pathological detection of amyloid deposition in biopsy samples of a subcarinal lymph node, gastric and duodenal mucosa, cardiac muscle, and bone marrow led to a diagnosis of primary systemic AL amyloidosis with nephrotic syndrome and cardiomyopathy. In addition, RAGE was detected in lung tumour tissues surrounded by normal lung tissues with amyloid deposition. CONCLUSION: The RAGE positivity of the lung cancer cells in this case suggests an interaction between amyloid-containing tissues and RAGE-expressing cancer cells. Lung adenocarcinoma with RAGE expression may be a complication of underlying amyloidosis.